External Debt Management in Low-Income Countries - Bangura, Sheku (IMF Working Papers; Working Paper, 2000)
Improving debt management capacity in Heavily Indebted Poor Countries (HIPCs) is a key element of the international community's strategy for ensuring a robust and sustained exit from unsustainable debt burdens. External debt management is a multi-facetted task involving the formulation of a transparent strategy for managing the level of debt, and establishing an appropriate institutional framework that supports effective implementation. This paper brings together the essential elements of effective debt management practices to guide for those assessing debt management capacity and advising on its improvement in low-income countries.